A Comparison of the Significances of Garuda in Society, Arts and Architecture in Two South-East Asian Countries: Indonesia and Thailand - and Onusa Suwanpratest, Andre Iman Syafrony (Journal of Community Development Research (Humanities and Social Sciences); Vol 9 No 1 (2559): January - April 2016, 2016)
The aim of this study is to compare the significance of the influence of Garuda on Indonesian and Thai cultures. A comparative study of the Garuda will help to enhance the understanding of the values that are specific to the Thai and Indonesian cultures as well as the cultural traits and identities that are shared across cultures in these two nations. Methodologically-wise, this study is a textual, qualitative and comparative study. The author surveys and collects the texts that contain Garuda motifs from texts in Indonesia and Thailand and online sources. The author analyzes the information through the comparative approach in terms of the importance of Garuda in Indonesia and Thailand, to look for similarities and differences in the conventions of society, art, performances and architecture. The study reveals that there are many reasons why the concept of Garuda is significant in these two countries. Taken as an example, the belief that the king is an incarnation of the god Vishnu is prevalent in both Indonesia and Thailand. In Indonesia, Garuda is seen as an important entity which represents the holy vehicle, bearing many divine traits. This view is also held in Thailand. It is why the two countries put so much importance on the symbol of Garuda. The visible difference is, in Indonesia, the Garuda is represented as being more bird-like, with an eagle-like face, while in Thailand the Garuda has a human like face with a bird-like body. In Indonesia, the Garuda is seen more as the symbol of virtues, while in Thailand, it is associated with the institute of kingship. It is because in many stories Garuda symbolizes the virtues of knowledge, power, bravery, loyalty, and discipline. As the vehicle of Vishnu, Garuda also bears the attributes of Vishnu, which symbolize the preservation of the cosmic order.  This is perhaps one of many reasons why the Indonesian founding-fathers adopted this image as the national emblem. While in Thailand, the symbol of Garuda is always associated with the institute of kingship, therefore, the symbol of Garuda stands for something sacred and holy; this is not the case in Indonesia, where the symbol of Garuda is seen more as the symbol of virtue.   Keywords: Garuda, Virtue, Indonesia and Thailand
Keywords: Garuda, Virtue, Indonesia and Thailand